Oral Discomfort And Impaired Oral Function In The Fixed Lingual Orthodontic Treatment - Akhyar Dyni Zakyah; Intan Sri Fajarwati (Sriwijaya Journal of Dentistry, 2020)
Introduction: Aesthetic consideration has become an important component for patients to decide the use of fixed orthodontic appliance, one of which is the fixed lingual orthodontic appliance. However, there are still many complaints about the discomfort felt by the patient that affects their compliance to the treatment. This paper aims to deliver the knowledge regarding oral discomfort and impaired oral function in the fixed lingual orthodontic treatment to be used as operator and patient education material. Materials and Methods: “lingual braces” was the sole keyword used in three journal databases (Google Scholar, ScienceDirect, and PubMed) resulted in 11 journals that was used in this paper. Results: complaints were mostly about speech disturbance (6 journals), discomfort on the tongue (5 journals), pain (1 journal), difficulty in cleaning the oral cavity (4 journals), difficulty in chewing and dietary changes (3 journals), and caries (2 journals). Discussion: discomfort arising during treatment was largely associated with the reduced space which was occupied by the tongue at rest. This resulted in the continuous contraction of the tongue muscles. The contraction increases discomfort and resulted in impaired oral functions such as speech and chewing. The use of bracket that is closer to the surface of the teeth can reduce complaints. Conclusion: the lingual orthodontic bracket position and type of the system used in the treatment affects the patient's comfort. Most of the discomfort appeared in the first 3 months of treatment and decreased with time.